The inclusion of parents of 4 graders of a public school in Armenia to improve their descriptive writing skills in English. (2016)
The present work shows how the inclusion of parents into the educational field helps their kids to reach a high development in the writing component in English. The research problem was divided into several aspects such as the lack of interest towards the second language, since parents feel that English will not help their kids in the future; the difficulty in having some time to monitor their kid’s progress due to the intensity of their job and the analphabetism expressed by some parents made them feel reluctant in participating. The project was developed with one student of 4th grade of Zuldemaida School in Armenia, through a qualitative method along with some observations, interviews and questionnaires.